Genomic Evidence That Governmentally Produced Cannabis sativa Poorly Represents Genetic Variation Available in State Markets - Vergara, Daniela; Huscher, Ezra L.; Keepers, Kyle G.; Pisupati, Rahul; Schwabe, Anna L.; McGlaughlin, Mitchell E.; Kane, Nolan C. (Frontiers in Plant Science, 2021)
The National Institute on Drug Abuse (NIDA) is the sole producer of Cannabis for research purposes in the United States, including medical investigation. Previous research established that cannabinoid profiles in the NIDA varieties lacked diversity and potency relative to the Cannabis produced commercially. Additionally, microsatellite marker analyses have established that the NIDA varieties are genetically divergent form varieties produced in the private legal market. Here, we analyzed the genome of multiple Cannabis varieties from diverse lineages including two produced by NIDA, and we provide further support that NIDA’s varieties differ from widely available medical, recreational, or industrial Cannabis. Furthermore, our results suggest that NIDA’s varieties lack diversity in the single copy portion of the genome, the maternally inherited genomes, the cannabinoid genes, and in the repetitive content of the genome. Therefore, results based on NIDA’s varieties are not generalizable regarding the effects of Cannabis after consumption. For medical research to be relevant, material that is more widely used would have to be studied. Clearly, having research to date dominated by a single, non-representative source of Cannabis has hindered scientific investigation.